Wendepunkt : Kunst in Europa um 1960. - Storck, Gerhard; Kaiser Wilhelm Museum, Krefeld (Krefeld : Museum Haus Lange, 1980)
Beuys, Joseph ; Klein, Yves ; Kounellis, Jannis ; Manzoni, Piero ; Rainer, Arnulf ; Lo Savio, Francesco ; Twombly, Cy
Wendepunkt : Kunst in Europa um 1960, Museum Haus Lange, Krefeld, 11. Mai - 6. Juli 1980
boek
Keywords: Europa